PERSONAL FACTORS AND THEIR PERSPECTIVE IN SOCIAL MEDICINE AND REHABILITATION - Seger, Wolfgang; Grotkamp, Sabine; Cibis, Wolfgang (International Journal of Research -GRANTHAALAYAH, 2017)
Motivation / Background: A broad and common understanding of the nature of Personal Factors is deemed to be necessary to gain and assess a comprehensive perspective regarding an individual’s health condition and accurately allocate social and medical benefits and interventions. Personal Factors have an impact on the functioning of individuals as facilitators or barriers. They play an essential role in the International Classification of Functioning, Disability and Health (ICF). To date, the World Health Organisation has not classified Personal Factors for global use. Method: A consensus group representing a broad spectrum of medical and social security professionals, research societies together with representatives of self-help organisations developed and published a proposal to classify relevant Personal Factors. Results: To face ongoing discussions misunderstandings are addressed, critics and suggestions balanced and positions created with pointed explanations and supplemented literature. Core messages summarise each position in a condensed form. Conclusions: Personal Factors may exert a powerful influence on the goal definition, goal achievement and type, complexity and length of necessary medical, social or rehabilitation benefits. Transparency, explicitness, fairness (standardisation) and the possibility for well-founded claims comprise additional arguments for reporting Personal Factors. They may be crucial to reach the goal of the highest degree of participation considering individual resources.